Efektivitas Program Magang Studi Independen Bersertifikat (MSIB) Kampus Merdeka Dalam Mengembangkan Kompetensi Mahasiswa di Social Economic Acceleator Lab (SEAL) - Rosalina, Sarah; Suherman, Enjang; Khalida, Laras Ratu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to evaluate the effectiveness of the Certified Independent Study Internship Program (MSIB) in developing students' competencies at the Social Economic Accelerator Lab (SEAL). The identified phenomenon indicates a mismatch between the majors chosen by students and their interests and abilities, which can hinder the learning process. The research method employed is descriptive qualitative, involving data collection through interviews and observations of students, mentors, and representatives from the Merdeka Campus.The results of the study indicate a significant improvement in students' skills after participating in the internship program, with average scores increasing from 66.30 to 86.139. Additionally, participants reported a high level of satisfaction with their internship experiences, while mentors noted that students were able to apply the skills acquired in the workplace. This research confirms that the MSIB program is effective in bridging the gap between higher education and industry needs, as well as providing practical experiences that enhance students' job readiness. Recommendations for program improvement include increasing support for mentors and providing initial training for students before entering the workforce.